Study of Technological Parameters of Fiber Separation Device - Azamatovich Obidov, Avazbek; Mirzarakhmatovich Sultanov, Mirzaolim (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the strength of a device designed to separate spinning fibers from fiber waste (lint) produced at a cotton gin. The study determined the resistance of the shaft to vibration as a result of periodic loading and the frequency of vibration along its axis through the critical rotational frequency.